2019
DOI: 10.3390/w11122593
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Residue Cover on Infiltration Process of the Black Soil Under Rainfall Simulations

Abstract: Residue cover is widely used for soil conservation after crop harvesting in the black soil region of the Northeastern China, which influences infiltration. It is necessary to optimize infiltration models for accurate predictions under bare and residue cover slope conditions. Rainfall simulation experiments were conducted to quantify the infiltration for the black soil under four rainfall intensities (30, 60, 90, and 120 mm/h), five residue coverage controls (15%, 35%, 55%, 75%, and bare slope), and two soil mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 29 publications
1
3
0
Order By: Relevance
“…The soil infiltration rate plays a pivotal role in surface runoff and exerts a substantial influence on SWL in sloping farmland. Typically, the soil water infiltration process follows a pattern characterized by an initial rapid infiltration rate that subsequently diminishes, eventually stabilizing (Xin et al, 2019). The results from our experiment revealed that the NT, in comparison to CK, demonstrated an enhanced soil infiltration capacity, corroborating the findings of (Ranaivoson et al, 2017), who attributed this enhancement to straw mulching and no-tillage practices, which effectively mitigated surface runoff while bolstering soil structure.…”
Section: Effects Of Tillage Methods On Soil Infiltration Characteristicssupporting
confidence: 82%
“…The soil infiltration rate plays a pivotal role in surface runoff and exerts a substantial influence on SWL in sloping farmland. Typically, the soil water infiltration process follows a pattern characterized by an initial rapid infiltration rate that subsequently diminishes, eventually stabilizing (Xin et al, 2019). The results from our experiment revealed that the NT, in comparison to CK, demonstrated an enhanced soil infiltration capacity, corroborating the findings of (Ranaivoson et al, 2017), who attributed this enhancement to straw mulching and no-tillage practices, which effectively mitigated surface runoff while bolstering soil structure.…”
Section: Effects Of Tillage Methods On Soil Infiltration Characteristicssupporting
confidence: 82%
“…The total sediment transport rate formula of Yang's arithmetic coefficients has been transformed into fuzzy numbers by Kaffas et al [35], resulting in a fuzzy relationship that has produced a fuzzy band of in-stream sediment concentration. Xin et al [36] observed simulated rainfall experiments to observe the infiltration processes of black soil slopes under bare and residue-covered situations. A study of the impact of ponds in limnologically rich basins on soil erosion and sediment transport has been reported by Al Sayah et al [37].…”
Section: Literature Reviewmentioning
confidence: 99%
“…Several studies have shown that the level of accuracy of the infiltration model (Horton, Kostiakov and Kostiakov Lewis) is quite good for field data with an R 2 value > 0.9 [14]. However, in several other research studies, the infiltration model produced less accurate results when compared to field data [19,20]. The analysis of related sources revealed that the behaviors of the infiltration models varied depending on the land use, climate, and field situations.…”
Section: Introductionmentioning
confidence: 98%
“…Higher model performance is indicated by a smaller RMSE value [5]. The RMSE statistics perform best when the value is close to zero [19].…”
mentioning
confidence: 99%